EFFECTIVE ORGANIZATION OF STILL LIFE LESSONS THROUGH NATIONAL VALUES - Rahimova Gulhayo Qahramonovna (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores the theoretical and practical foundations of organizing still life (natyurmort) lessons in visual arts education based on national values. It emphasizes the importance of integrating traditional culture, folk art, and national symbolism into art lessons to enhance students’ aesthetic perception, artistic thinking, and creative expression. The study discusses methods for using national motifs in still life compositions and highlights the role of teachers in fostering cultural awareness and appreciation of heritage through visual representation. The paper also provides methodological recommendations for effectively organizing still life classes using modern pedagogical and digital technologies.